Analisis Hubungan Kepadatan Penduduk dengan Pola Penyebaran COVID-19 Provinsi DKI Jakarta menggunakan Regresi Robust - Edriani, Tiara Shofi; Rahmadani, Anisa; Noor, Dear Michiko Mutiara (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
COVID-19 pandemic have been spread around the world since the first outbreak on Desember 2019 in Wuhan, China. DKI Jakarta as one of the highest population density among 34 provinces in Indonesia, has become an endemic area of COVID-19 with the rate of new cases show some fluctuation for each month along 2020. This is a secondary data research which drawn from Health Ministry of Indonesia as well as Center of Statistics for DKI Jakarta. Focus and the scope of this paper is on analyzing the relation between new cases of COVID-19 with population density of Jakarta’s districts. Descriptive and inferential analysis that combined with Robust Regression Test are conducted due to some outliers data. This unbiased method shows a good regression model of spreading new positive cases. M-Estimator Robust Regression with Tukey Bisquare function, shows the best result with the least Residual Standar Error (RSE), that is 0.411. Analysis on statistical test for the chosen model shows that population density has significant impacts on outbreak pattern of COVID-19 in Jakarta. But mobilities and interactions betweeen citizens has also give a great impact.